Facioscapulohumeral muscular dystrophy functional composite outcome measure. Issue 1 (20th February 2018) - Eichinger, Katy; Heatwole, Chad; Iyadurai, Stanley; King, Wendy; Baker, Lindsay; Heininger, Susanne; Bartlett, Amy; Dilek, Nuran; Martens, William B.; Mcdermott, Michael; Kissel, John T.; Tawil, Rabi; et al.
ABSTRACT: Introduction : We developed an evaluator‐administered functional facioscapulohumeral muscular dystrophy composite outcome measure (FSHD‐COM) comprising patient‐identified areas of functional burden for future clinical trials. Methods : We performed a prospective observational study of 41 patients with FSHD at 2 sites. The FSHD‐COM includes functional assessment of the legs, shoulders and arms, trunk, hands, and balance/mobility. We determined the test‐retest reliability and convergent validity compared to established FSHD disease metrics. Results : The FSHD‐COM demonstrated excellent test‐retest reliability (intraclass correlation coefficient [ICC] 0.96; subscale ICC range, 0.90–0.94). Cross‐sectional associations between the FSHD‐COM and disease duration, clinical severity, and strength were moderate to strong (Pearson correlation coefficient range |0.51–0.92|). Discussion : The FSHD‐COM is a disease‐relevant, functional composite outcome measure suitable for future FSHD clinical trials that shows excellent test‐retest reliability and cross‐sectional associations to disease measures. Future directions include determining multisite reliability, sensitivity to change, and the minimal clinically important change in the FSHD‐COM. Muscle Nerve 58 : 72–78, 2018